Analyzing Decision-making Bias in Female CEOs through the Lens of Behavioral Strategy - Masoumeh Hosseinzadeh Shahri (مطالعات اجتماعی روان‌شناختی زنان)
Managers face with cognitive and behavioral biases in their judgments and decisions in the organization, which are the main cause of misjudgments and disagreements in many situations. The purpose of this study is to examine the decision biases of female CEOs in the context of behavioral strategy. Although women have made progress in leadership positions, unconscious bias, social expectations and organizational structures still hinder their full participation and influence strategic initiatives. This research is applied research with a qualitative approach and using thematic analysis. The data was obtained through in-depth interviews with 15 female managers and continued until theoretical saturation. Data analysis was conducted using Max QDA2020 software. A total of 76 primary codes, 18 sub-themes and 13 main themes were extracted, which were categorized into three categories. Affective/emotional bias, cognitive bias and gender stereotype bias are the three main categories of bias in the decisions of female CEOs. Affective/emotional biases include the following four biases: prior emotional stimuli, overoptimism, emotional contagion, and fear of potential loss. Cognitive biases include five: Information processing bias, memory bias, lack of attention in decision making, judgment bias, and overconfidence. Gender stereotypes include multiple roles, social expectations and norms, perfectionism and comparison with male peers. By identifying and understanding these biases, it is possible to understand the unique challenges and opportunities of women managers in complex strategic decision-making and to contribute to a more accurate understanding of the factors that shape the leadership behaviors and decision-making of female CEOs in organizations.